The complete chloroplast genome of Aquilaria malaccensis Lam. (Thymelaeaceae), an important and threatened agarwood-producing tree species - Lee, Shiou Yih; Wei, Lun Ng; Mohamed, Rozi; Terhem, Razak (Taylor & Francis Open, 2018)
Known for its valuable agarwood, Aquilaria malaccensis Lam. is an evergreen tropical forest tree species endemic to the Indo-malesian region. Indiscriminate damaging and harvesting of the trees in the wild have resulted in it being listed in the CITES Appendix II for controlled trade and in the IUCN Red List as ‘Vulnerable (VU)’. In this study, the complete chloroplast genome of A. malaccensis was assembled using data from high-throughput Illumina sequencing. The chloroplast genome was 174,832 bp in size, which included two inverted repeat regions of 42,091 bp each, separated by a large single copy region of 87,302 bp and a small single copy region of 3,348 bp. A total of 139 genes were predicted, including 39 tRNA, 8 rRNA, and 92 protein-coding genes. Phylogenetic analysis placed A. malaccensis within the family Thymelaeaceae. The chloroplast genome sequence of A. malaccensis offers a useful resource for future studies on the taxonomy and conservation of the threatened Aquilaria trees.